Reorganización Contable en la Empresa del Sr. Padilla Armijos Darwin de la Ciudad de Loja, periodo del 1 de abril al 30 de junio del 2023. - Patiño Torres., Anabel Estefanía (2024)
The Curricular Integration Work called: Reorganización Contable en la Empresa del Sr. Padilla Armijos Darwin de la Ciudad de Loja, periodo del 1 de abril al 30 de junio del 2023, was developed with the purpose of providing the owner with an efficient and solid accounting structure that allows him to know the economic and financial situation of the entity and in turn make decisions that promote the achievement of business objectives. In order to fulfill the objectives, we began with the preparation of a plan and manual of accounts structured according to the nature and activity of the company, then the Initial Inventory was made through the physical verification of all the values, goods and obligations it owns, for which a total of assets amounting to 436,722.96, liabilities of 136,613.84 and equity of 300,109.12 were determined, information that was used for the preparation of the Initial Situation Statement. Then, through the compilation and analysis of the source documentation, the auxiliary records of purchases, sales, documents payable and receivable were designed, which allowed for the orderly and systematic preparation of the daily ledger; the multiple account system was applied for the control of the merchandise; The general ledger was then developed in order to know the movement and balance of each account; the trial balance to verify the equality between debtor and creditor balances; the work sheet made possible the synthesis of all accounting operations; and finally, the financial statements were obtained: Statement of Financial Position, Income Statement, Cash Flow Statement and culminated with the preparation of the Explanatory Notes where additional and significant data presented in the development of the Financial Statements were disclosed. This information is key for the owner to make decisions that address deficiencies and improve the profitability of the company.